The Application of Classical Music Therapy in Reducing Pain Levels in Post Operative Fracture Patients - Putri, Vemya Agustiara Nursaini; Khumaidi, Khumaidi; Handayani, Sri Endah (Fakultas Kedokteran, 2025)
AbstractIntroduction: Fractures often cause postoperative pain that can hinder recovery. Classical music therapy, particularly Mozart’s compositions, has been proven effective as a non-pharmacological intervention to reduce pain through mechanisms involving the central nervous system and stress hormones. This method is non-invasive, safe, and easy to apply. This study aims to explore the application of Mozart’s classical music therapy in reducing pain intensity in post-operative fracture patients, as a means to support holistic nursing approaches and enhance patient comfort during the recovery period. Methode: The method used was a case study with an evidence-based nursing practice approach involving two post-operative fracture patients at Inche Abdoel Moeis Hospital. The pain level was measured using the Numeric Rating Scale (NRS) after the administration of classical music therapy by Mozart. Result: The pain levels of both clients showed a significant decrease after receiving Mozart classical music therapy for 20 minutes, once a day for three consecutive days. Before the intervention, Mr. D reported a pain level of 6 and Mr. I reported a level of 5 on the Numeric Rating Scale (NRS). After the intervention, both of their pain levels decreased to 3 on the third day of evaluation. Conclusion: Classical music therapy by Mozart in two post-operative fracture patients showed a reduction in pain both clinically and subjectively. The music promoted relaxation, diverted attention from pain, and stimulated the body's natural analgesics. This intervention is effective, low-risk, and suitable for implementation as a non-pharmacological strategy in holistic nursing care. Keywords: Pain, Post-Operative Fracture, Classical Music Therapy, Mozart